Analysis of Entrepreneurship Education and Training On Entrepreneurial Motives : Case Study on Students at Vocational Schools in Mojokerto City - Nuryanti, Rizky; Haqi, Syafrozi; Sudarmiatin; Firmansyah, Rizky (PT. Maju Malaqbi Makkarana, 2024)
This study aims to analyze how entrepreneurship education and training affect entrepreneurial motives in vocational school students in Mojokerto City. Using a qualitative approach with a case study method, this study explores students' experiences, perceptions, and views regarding the learning process and entrepreneurship training they receive. Data were obtained through in-depth interviews, participatory observations, and document analysis from several vocational schools that were the subject of the research. The results of the study show that entrepreneurship education has a significant influence on students' mindset and attitude towards entrepreneurship, especially in building confidence and courage to start a business. Meanwhile, entrepreneurship training provides students with hands-on experience in developing practical skills relevant to the business world. Supporting factors such as teacher involvement, training facilities, and school support play an important role in maximizing the impact of education and training. This study concludes that integrated entrepreneurship education and training can encourage students to have a stronger entrepreneurial motive. As a recommendation, it is necessary to develop a more applicable and local potential-based entrepreneurship learning model to increase its relevance and effectiveness.